Pengaruh Kompetensi, Etika Auditor dan Teknologi Informasi Terhadap Kualitas Audit (Studi Empiris pada KAP Kota Malang) - Aryundah Siwi Faryantri; Anik Malikah; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The increasingly transparent era of globalization requires that every company is more competent in presenting financial reports. The reports presented must be in accordance with applicable accounting principles so that they can be well received by interested parties in making decisions. In this case, the importance of the role of the auditor as a liaison between the interests of investors as users of financial reports and companies as providers of financial reports. Therefore, it is necessary to carry out an audit of the financial statements in determining an opinion on the financial statements. The goal of this study was to find out how information technology, auditor ethics, and competence affect audit quality. Sampling obtained 40 respondents based on the criteria applied. This study uses a multiple linear regression model. The results of this study indicate that competence, auditor ethics and information technology have a significant positive effect on audit quality. Competence has a significant positive effect on audit quality. Audit quality is significantly improved by auditor ethics. Audit Quality is significantly improved by information technology.Keywords: Competence, auditor ethics, information technology, audit quality.